Plant mutualisms with rhizosphere microbiota in introduced versus native ranges. (September 2016) - Shelby, Natasha; Duncan, Richard P.; van der Putten, Wim H.; McGinn, Kevin J.; Weser, Carolin; Hulme, Philip E.
Summary: The performance of introduced plants can be limited by the availability of soil mutualists outside their native range, but how interactions with mutualists differ between ranges is largely unknown. If mutualists are absent, incompatible or parasitic, plants may compensate by investing more in root biomass, adapting to be more selective or by maximizing the benefits associated with the mutualists available. We tested these hypotheses using seven non‐agricultural species of Trifolium naturalized in New Zealand (NZ). We grew seeds from two native (Spain, UK) and one introduced (NZ) provenance of each species in glasshouse pots inoculated with rhizosphere microbiota collected from conspecifics in each region. We compared how plant biomass, degree of colonization by rhizobia and arbuscular mycorrhizal fungi (AMF), and the growth benefit associated with each mutualist differed between provenances (native and introduced populations) when grown with soil microbiota from each region. We also tested whether the growth benefit of colonization by mutualists was correlated with the extent to which alien plants were distributed in the introduced range. Rhizobia colonization was generally lower among introduced relative to native provenances. In NZ soils, 9% of all plants lacked rhizobia and 16% hosted parasitic nodules, whereas in native‐range soils, there was no evidence of parasitism and all but one plant hosted rhizobia. Growth rates as a factor of rhizobia colonization were always highest when plants were grown in soil from their home range. Colonization by AMF was similar for all provenances in all soils but for four out of seven species grown in NZ soils, the level of AMF colonization was negatively correlated with growth rate. In general, introduced provenances did not compensate for lower growth rates or lower mutualist associations by decreasing shoot–root ratios. Synthesis . Despite differences between introduced and native provenances in their associations with soil mutualists and substantial evidence of parasitism in the introduced range, neither level of colonization by mutualists nor the growth benefit associated with colonization was correlated with the extent of species' distributions in the introduced range, suggesting mutualist associations are not predictive of invasion success for these species. Abstract : Using a biogeographical approach, we compare how seven species of Trifolium, each sourced from the native (Europe) and introduced (New Zealand) ranges, differ in their performance and their degree of colonization by mutualists (rhizobia and arbuscular mycorrhizal fungi) when grown in soils sourced from each range.